Save the cat! writes a novel : the last book on novel writing you'll ever need - Brody, Jessica (Ten Speed Press, 2018)
"The first novel-writing guide from the best-selling Save the Cat! story-structure series, which reveals the 15 essential plot points needed to make any novel a success. Novelist Jessica Brody presents a comprehensive story-structure guide for novelists that applies the famed Save the Cat! screenwriting methodology to the world of novel writing. Revealing the 15 "beats" (plot points) that comprise a successful story--from the opening image to the finale--this book lays out the Ten Story Genres (Monster in the House; Whydunit; Dude with a Problem) alongside quirky, original insights (Save the Cat; Shard of Glass) to help novelists craft a plot that will captivate--and a novel that will sell"--